Epstein‐Barr virus‐immortalized B lymphocytes exacerbate experimental autoimmune encephalomyelitis in xenograft mice. Issue 6 (5th October 2020) - Polepole, Pascal; Bartenslager, Alison; Liu, Yutong; Petro, Thomas M.; Fernando, Samodha; Zhang, Luwen
Abstract: Multiple sclerosis (MS) is the most common autoimmune disorder affecting the central nervous system. Epstein‐Barr virus (EBV) is a causative agent for infectious mononucleosis (IM) that is associated with MS pathogenesis. However, the exact mechanism by which EBV, specifically in IM, increases the risk for MS remains unknown. EBV immortalizes primary B lymphocytes in vitro and causes excessive B lymphocyte proliferation in IM in vivo. In asymptomatic carriers, EBV‐infected B lymphocytes still proliferate to certain degrees, the process of which is tightly controlled by the host immune systems. Experimental autoimmune encephalomyelitis (EAE) mimics key features of MS in humans and is a well‐established rodent model for human MS. We have found that xenografts of EBV‐immortalized B lymphocytes, which partially resemble the hyperproliferation of EBV‐infected cells in IM, exacerbate autoimmune responses in myelin oligodendrocyte glycoprotein‐induced EAE in C57BL/6 mice. After remission, an additional challenge with EBV‐immortalized cells induces a relapse in EAE. Moreover, xenografts with EBV‐immortalized cells tighten the integrity of the blood‐brain barrier (BBB) in the thalamus and hypothalamus areas of the mouse brains. Genomic sequences of prokaryotic 16S ribosomal RNA presented in the feces reveal that EBV‐immortalized cells significantly change the diversities of microbial populations. Our data collectively suggest that EBV‐mediated proliferation of B lymphocytes may be a risk factor for the exacerbation of MS, which are associated with gut microbiome changes and BBB modulations. Furthermore, multiple xenografts of EBV‐immortalized cells into C57BL/6 mice could serve as a useful model for human relapsing‐remitting MS with predictable severity and timing. Highlights: Mimic infectious mononucleosis with Epstein‐Barr virus (EBV)‐immortalized cells enhances experimental autoimmune encephalomyelitis in C57BL/6 mice. Changes in blood‐brain barrier and microbiome are associated with the enhancement. Multiple exposure of EBV‐immortalized cells could serve as a model for human relapsing‐remitting multiple sclerosis with predictable severity and timing